PENGARUH PERSEPSI PELAKSANAAN SENSUS PAJAK NASIONAL, PENGETAHUAN DAN PEMAHAMAN PERATURAN PERPAJAKAN, DAN KESADARAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (WPOP) PADA KPP PRATAMA PEKANBARU SENAPELAN - Maslyn Eva Uli Siahaan; Yesi Mutia Basri; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted to determine the effect of Perception of national tax census, knowledge and understanding of taxation laws, tax awareness, with taxpayers compliance personal. This research conducted on Pekanbaru Senapelan tax services office (KPP). The population in this rearch was all taxpayer listed in Pekanbaru Senapelan tax service office (KPP). This study uses purposive sampling with a sample size of 100 respondent. This research uses primary data questionnaire. This research used quantitative methods with multiple regression analysis models. Partial regression test showed that Perception of national tax census, knowledge and understanding of taxation laws has positive effect to the taxpayer compliance personal and variable tax awarenes has not effect to the taxpayer compliance personal. The magnitude of the effect caused by Adjusted (R2) by three independent variables is 44,3%, while the remaining 55,7% is influenced by other variables not examined in this study.Keywords: Perception, census, knowledge, tax, and compliance